2015
DOI: 10.1038/srep13858
|View full text |Cite
|
Sign up to set email alerts
|

Superiority of Graphene over Polymer Coatings for Prevention of Microbially Induced Corrosion

Abstract: Prevention of microbially induced corrosion (MIC) is of great significance in many environmental applications. Here, we report the use of an ultra-thin, graphene skin (Gr) as a superior anti-MIC coating over two commercial polymeric coatings, Parylene-C (PA) and Polyurethane (PU). We find that Nickel (Ni) dissolution in a corrosion cell with Gr-coated Ni is an order of magnitude lower than that of PA and PU coated electrodes. Electrochemical analysis reveals that the Gr coating offers ~10 and ~100 fold improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 52 publications
0
30
0
Order By: Relevance
“…Finally, graphene can also play the role of a diffusion barrier, preventing toxic release from the probe and acting as a corrosion protection for the metal‐based electrodes that could also contribute to reduce the immune reaction . Regarding the slow degradation of graphene, the presence of graphene should still prevent the surface ions to diffuse out of the implant during the paroxysm of the inflammation (i.e., during the first week), and thus allow a better healing around the probe.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, graphene can also play the role of a diffusion barrier, preventing toxic release from the probe and acting as a corrosion protection for the metal‐based electrodes that could also contribute to reduce the immune reaction . Regarding the slow degradation of graphene, the presence of graphene should still prevent the surface ions to diffuse out of the implant during the paroxysm of the inflammation (i.e., during the first week), and thus allow a better healing around the probe.…”
Section: Discussionmentioning
confidence: 99%
“…Besides its use as reinforcing filler, graphene is used as a coating in conventional materials for inducing multi-functionality 10 . Various graphene coated applications have been demonstrated such as gilding of large structures 4 and protection from corrosion 11 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that, factoring in the growth-induced defects, transferring a 2D material can further deteriorate the 2D material structure (Figure 8) [18]. For example, researchers have found that as grown graphene on a rough metal substrate, if transferred to a target substrate, provides poor 2D material quality (i.e., higher defect density).…”
Section: Transfer-induced Defectsmentioning
confidence: 99%
“…Organic and polymer coatings have a relatively large thickness (up to several microns), which could adversely affect thermal and electrical conductivity as well as the component dimensionality [17]. Many traditional polymer coatings are susceptible to microbial corrosion, high-temperature degradation, and have inherent porosity [14,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation